P-621 Different gonadotrophins adopted for controlled ovarian stimulation do not affect metaphase-II oocyte competence. A matched case-control study on 351 patients and 2258 oocytes. (30th June 2022) - Scarafia, C; Vaiarelli, A; Cimadomo, D; Amendola, M.G; Colamaria, S; Argento, C; Giuliani, M; Ferrero, S; Gennarelli, G; Revelli, A; Benedetto, C; Alviggi, C; et al.
Abstract: Study question: Do different gonadotrophins for controlled-ovarian-stimulation (COS) affect metaphase-II (MII) oocyte competence? Summary answer: Euploid blastocyst rate (EBR) per cohort of MII-oocytes, live-birth-rate (LBR) per first vitrified-warmed euploid single-embryo-transfer (SET) and cumulative-LBR are independent from the gonadotrophins used. What is known already: Controlled-ovarian-stimulation (COS) is a cornerstone of IVF. Its purpose is maximizing ovarian reserve exploitation and obtaining ≥1 euploid blastocyst to transfer. Indeed, ovarian reserve decreases and blastocyst aneuploidy rates increase with increasing maternal age, making this task quite complicated in advanced maternal age. Old-fashioned studies suggested an association between COS and embryonic aneuploidy rates. Conversely, recent studies excluded an impact of COS dosage, duration, ovarian response, and ovulation trigger, on blastocyst aneuploidy rate. An aspect, though, needs more clarity: do different gonadotropins impact oocyte competence after COS, comprehensively defined as EBR per cohort of MII-oocytes? Study design, size, duration: Out of 3169 PGT cycles with ³1 MII oocyte conducted between 2014-2018, we excluded (i)PGT-M/-SR, (ii)women<35yr, (iii)severe-male-factor, (iv)DuoStim or long-active FSH, (v)culture with sequential-media, and (v)multiple cycles. Among the 784 cycles left, a propensity-score-matching (PSM) based on the number of inseminated MII-oocytes was adopted to match patients using recFSH [without (N = 57; 337 MII-oocytes)/with recLH (N = 55; 374 MII-oocytes)] and Human-Menopausal-Gonadotrophin (HMG; N = 127; 835 MII-oocytes). The patients using recFSH+HMG were all included (N = 112; 712 MII-oocytes). Participants/materials, setting, methods: Only GnRH-antagonist COS, ICSI with fresh MII-oocytes, single culture in continuous-media, trophectoderm biopsy without assisted-hatching, comprehensive-chromosome-testing to assess full-chromosome non-mosaic aneuploidies and vitrified-warmed euploid SET were conducted. Oocyte competence was comprehensively defined as EBR per cohort of MII-oocytes with all intermediate outcomes (fertilization, blastulation and euploidy). LBR per first vitrified-warmed euploid SET and cumulative-LBR per retrieval were also assessed. Generalized-linear-models and multivariate regressions were adopted to adjust the results for confounders. All cycles were concluded. Main results and the role of chance: Patients using recFSH+recLH and recFSH+HMG (40.7 yr) were older than patients using recFSH-only or HMG-only (40 yr; ANOVA<0.01). No other difference was reported in the 4 patient populations. The overall gonadotrophins dosage (2615±977, 3601±1889, 3818±946 and 2892±911 IU in the recFSH-only, recFSH+recLH, recFSH+HMG and HMG-only groups, respectively) and duration of COS (9.7±1.9, 9.4±1.5, 9.9±1.8 and 10.2±1.8 days) were different (Kruskal-Wallis tests=0.02). The number of cumulus-oocyte-complexes (9.2±6.5) and MII-oocytes collected (6.4±4.4) were instead well-matched across the groups. The EBR per cohort of inseminated MII-oocytes was different in the four groups (20.7±27.1%, 9.6±12.9%, 12.4±18.5% and 16.9±21.8%, respectively), but, when adjusted for maternal age in a generalized-linear-model, the gonadotrophin used for COS did not show any significant association with this outcome (partial-eta 2 =0.02, p = 0.1, power=0.6). All intermediate embryological outcomes were also similar. The LBR per first vitrified-warmed euploid SET was comparable in the four groups [N = 14/33 (42%), N = 9/22 (41%), N = 26/62 (45%), N = 24/55 (44%), respectively], as confirmed by the logistic regression adjusted for blastocyst quality (multivariate-OR: 0.97, 95%CI 0.73-1.31, adjusted-p=0.9). Lastly, the cumulative-LBRs per retrieval were equivalent [N = 17/57 (30%), N = 14/55 (26%), N = 34/127 (27%), and N = 33/112 (30%), respectively], as confirmed by the logistic regression adjusted for maternal age (multivariate-OR: 1.01, 95%CI 0.8-1.3, adjusted-p=0.9). Limitations, reasons for caution: The gonadotrophins were chosen based on patient compliance to their administration route and gynecologist judgement, and only qualitative outcomes were assessed. Therefore, randomized-controlled-trials and cost-effectiveness analysis investigating the efficiency in oocyte recruitment and cumulative-LBR per intention-to-treat are needed. Wider implications of the findings: Different gonadotrophins might not affect MII-oocyte competence. This information is key since, in view of the optimization of follicle recruitment through personalized-COS, it allows more flexibility in the choice of the most suitable protocol. Therefore, gynecologists might ponder also features like patient reproductive history and compliance to different administration routes. Trial registration number: none